Power-force-velocity profile in countermovement jump - Jimenez Reyes, P.; Samozino, P.; Conceicao, F.; González Badillo, J. J.; Cuadrado Penafiel, V.; Morin, J.-B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Explosive performances directly depend on lower limb maximal power (Pmax) (Yamauchi et al 2007). Recently, Samozino et al showed that squat jump (SJ) performance was determined by both Pmax and mechanical force-velocity (FV) profile describing the ratio between force and velocity capabilities (Samozino et al 2012, 2013). However, SJ does not represent natural explosive movements due to the absence of the typical countermovement just before the jump (Markström 2013). The aims of this study were (i) to analyse the effect of countermovement on lower limb F-v relationship and (ii) to experimentally test the theoretical influence of FV profile on countermovement jumping (CMJ) performance, independently from the effect of Pmax. 54 high-level athletes performed maximal CMJ and SJ against additional loads. From vertical ground reaction force and displacement data, individual linear FV relationships were determined using the best trial for each condition. Individual mechanical FV imbalance (FVimb) was determined as the difference between actual and optimal FV profiles. FV relationships in CMJ were linear and shifted towards both greater force and velocity compared to SJ. A multiple regression analysis showed (r2=0.952, P<0.001, SEE=0.011 m) that both Pmax and FVimb explained a significant part of the interindividual differences in CMJ performance (P<0.001) with positive regression coefficients for Pmax and a negative for FVimb. Compared to SJ, CMJ FV relationships were shifted to the right, with higher Pmax, maximal theoretical force and velocity (+35.8, 20.6 and 13.3%, respectively). CMJ performance depends on FVimb, independently from the effect of Pmax, with the existence of an individually optimal F-v profile. The lower the FVimb, the greater the CMJ performance, which is of interest since it is a more specific physical test, and it has been related to performance in many sports (e.g. Comfort et al 2014). Coaches should quantify and consider individual FVimb to orient and individualize training loads and exercises to optimize the FV profile while increasing Pmax, and in turn performances. Moreover, a simple method has been recently validated to determine the individual Pmax, FV profile and FVimb of athletes using loaded CMJ in field conditions (in progress).